MARTIN, Craig. Masking Hegemony: A genealogy of liberalism, religion and the private sphere. London: Equinox, 2010. - Santos, Renan (Debates do NER, 2012)
MARTIN, Craig. Masking Hegemony: A genealogy of liberalism, religion and the private sphere. London: Equinox, 2010.